Charisma and the Fictions of Black Leadership - Edwards, Erica R. (Erica Renee) (Book collections on Project MUSE., 2012)
Social and political change is impossible in the absence of gifted male charismatic leadership -- this is the fiction that shaped African American culture throughout the twentieth century. If we understand this, Erica R. Edwards tells us, we will better appreciate the dramatic variations within both the modern black freedom struggle and the black literary tradition.